Reflecting on COVID-19 vaccine hesitancy among South Asian communities in the UK: A learning curve to decolonising the secondary school curriculum - Hu, Anqi; Nissan, Tracy; Pranjol, Md Zahidul Islam (Frontiers in Education, 2023)
COVID-19 has brought to light the systemic racism faced by ethnic minorities in the UK. During the pandemic, we saw an increase in anti-Asian hate crimes and a lack of support from the government given to both patients and healthcare workers from minority backgrounds on the front lines. This lack of support potentially contributed to the increased susceptibility of ethnic minorities to COVID-19 and also their hesitancy towards the vaccine, particularly the south Asian communities. In this paper we discuss potential reasons for COVID-19 vaccine hesitancy among south Asian groups. Additionally, we propose that introducing a decolonised curriculum in secondary school may enhance cultural awareness with historical context among the white British populations, allowing for more inclusion for south Asian communities. By exploring ways to decolonise specific subjects in the secondary curriculum, this paper aims to set out a guideline for teachers and education professionals on expanding secondary school pupils’ knowledge of racial issues and equality, to start the process of educating a new generation the right way. We propose that decolonising the secondary school curriculum is a potential long-term solution to eradicating racism and discrimination.